Fever of Unknown Origin (FUO): towards uniform definitions and classification system - Bosilkovski, Mile; Baymakova, Magdalena; Dimzova, Marija (Kare Publishing, 2020)
Despite the great advancement seen in the medicine in the last years, FUO remains to be a serious diagnostic challenge. Regardless of the etiological elucidation in many cases of FUO as well as the progress seen in the management of these patients, even nowadays there are many weaknesses in this sphere as a result of the collective inconsistency in defining and interpretation of the key terminology and the utilization of different definitions and classifications. As a result, there is a common confusion in the medical practitioners about FUO which leads towards laborious and incapable comparisons between different series. This study outlines the mismatching in terminology and diversities found in the classification of the conditions that cause FUO and points out the discrepancies between what some terminology should represent, and what actually embodies in reality. In this way we are attempting to find an appropriate solution in the established inconsistencies.